Classification of Regional Labour Markets At the NUTS3 Level in Germany - Uwe Blien; Felix Rueb; Daniel Werner; Katja Wolf (European Regional Science Association (ERSA), 2006)
In many countries labour market policy has to deal with fairly large and persistent regional labour market disparities. In the case of Germany, parts of the country are affected by a deep unemployment crisis whereas others show nearly full employment. Since these disparities cannot be reduced to only one dimension a classification system of labour markets was developed. The criterion of this system was the identification of the "regional disadvantage" for the success of labour market policy. This new classification is at the level of districts (NUTS 3 regions). To optimise the results a two-step classification method was applied. The first step included regression analyses to identify the exogenous determinants of the success of labour market policy. In the second step, different types of labour markets are determined from a specific variant of cluster analysis which used the weighted variables identified as significant in the first step. This classification is used in the Federal Employment Agency for benchmarking reasons. Besides that, the new classification obtained could also be employed in research, for example in the evaluation of labour market policy.
Keywords: 330